COGNITIVE COMPETENCY EARLY CHILDREN MEMORIZING THE QUR'AN OBTAINED FROM THE TAHFIDZ AL-QUR'AN LEARNING PROCESS - Sriyanto, Agus; Sumarno; Lutfi Gesang Saputra, Alan (LPPM STAI Muhammadiyah Probolinggo, 2023)
This research aims to explain the cognitive competencies that are formed in the process of learning tahfidz al-Qur'an. This research will be conducted using a qualitative research approach. Researchers will collect data using observation, interviews and documentation methods. Observations were carried out to obtain data about the process of learning tahfidz Al-Qur'an as well as various interactions that occurred inside and outside the classroom. Through observation, information will be obtained about the approaches, models, methods and learning techniques used so that data can be obtained about the competencies developed in learning tahfidz al-Qur'an. Furthermore, to obtain an in-depth understanding of the data obtained, researchers will use interviews with both students and institutional management. The research locus was ABA 2 Ngawi Kindergarten with 4 informants determined using purposive sampling techniques. The results of the research show that (1) The cognitive competence of early childhood is learning to solve problems, learning logically and thinking symbolically, (2) The cognitive competence of children after memorizing the Al-Qur'an is: memory improves well, children's concentration develops optimally, Coordination ability children develop well, text analysis skills develop well, multitasking abilities increase, emotional intelligence abilities increase, and fighting power and discipline increase, (3) Early Childhood tahfidz Qur'an learning methods applied at ABA 2 Ngawi Kindergarten are: With intensive guidance, providing motivation, and familiarization before every class study